134 VANTAGE Trial: Three-Year Outcomes of a Prospective, Multicenter Trial Evaluating Deep Brain Stimulation With a New Multiple-Source, Constant-Current Rechargeable System in Parkinson Disease. (1st August 2016) - Timmermann, Lars; Jain, Roshini; Chen, Lilly; Brucke, Thomas; Seijo, Fernando; San Martin, Esther Suarez; Haegelen, Claire; Verin, Marc; Visser-Vandewalle, Veerle; Barbe, Michael T.; Gill, Steven; Whone, Alan; et al.
Abstract: INTRODUCTION: Deep brain stimulation (DBS) has been demonstrated to be effective for Parkinson disease (PD) symptom relief. We sought to characterize the benefit of subthalamic nucleus (STN) DBS for PD patients using a recently CE-marked multiple-source, constant-current system that permits a well-defined distribution of applied current. We report the 3-year results of the first clinical trial using multiple independent current control (MICC) DBS in the management of symptoms of PD. METHODS: VANTAGE is a monitored, prospective, multicenter, nonrandomized, open-label interventional trial sponsored by Boston Scientific Corporation. Forty subjects with idiopathic PD were implanted bilaterally with a DBS system (Vercise) targeting the STN and followed up to 3 years after lead placement. Motor improvement was evaluated using Unified Parkinson's Disease Rating Scale (UPDRS) III scores in stim ON/meds OFF in comparison with preoperative scores. Other assessments such as CAPSIT motor tests, Tremor Rating Scale, Dyskinesia Rating Scale, PDQ-39, SF-36, Schwab and England, and resource utilization were administered. Patient motor diaries were collected over 3 days. Adverse events were also recorded. RESULTS: This study will report the safety and effectiveness outcomes of VANTAGE subjects at 3 years postimplantation as compared with baseline. CONCLUSION: The VANTAGE trial is the first reported trial of a multiple-source, constant-current rechargeable system for use in the management of PD symptoms. Study outcomes will inform clinicians on the use of this system and its flexibility to manage the symptoms of idiopathic PD.